Answers

2015-06-26T16:41:24+05:30
(3t+1) /16 - (t+3) /8 = (3t-1)/14 + (2t-3) /7 
(3t - 1 - 2(t+3) )/ 16 = (3t - 1 + 2( 2t- 3) )/ 14 
(3t -1 - 2t - 6) /16 = (3t -1 + 4t - 6)/ 14
( t - 7) / 16 = (7t - 7) 14 
(t - 7) / 16 = t - 1 
t - 7 = 16t - 16 
16t -t = -7 + 16 
15t = 9 
t = 9 /15 
t = 3 /5 
0
2015-06-26T16:46:49+05:30
(3t+1)/16-(2t-3)/7=(t+3)/8+(3t-1)/14
lcm of 16,7,8 and 14 is=112
multiply each term by 112
(3t+1)/16*112-(2t-3)7*112=(t+3)/8*112+(3t-1)/14*112
 (3t+1)*7-(2t-3)16=(t+3)*14+(3t-1)*8
21t+7-32t+48=14t+42+24t-8
21t-32t-14t-24t=42-8-7-48
21t-70t=42-63
-49t=-21
t=21/49
0